A model for addressing parallelism of systems in the management of data: The Namibian case. Issue 6 (19th September 2018) - Shaanika, Irja; Maletzky, Monica; Iyamu, Tiko
Abstract : As in many countries, the volume of data that has been generated by the Namibian government administrations and agencies in recent years has increased drastically in rapidity. Consequently, this has led to difficulties and challenges in the control and management of the voluminous data. These challenges arise from inconsistency, unavailability and duplications, which are caused by the nature of the huge data. Thus, the Namibian government deployed different systems — 'paper-based' system, electronic record management system (ERMS) and information management system (IMS) — to manage their data in order to gain efficiency and effectiveness, towards improved service delivery to society. However, the 'paper-based' and computerized systems collide with each other, causing more complexities and challenges in the management and control of data, which manifests negatively during decision making. This article therefore discusses the systems parallelism including the challenging factors and their implications. Also presented in the article is a data management model (DMM) which could be used in addressing some of the challenges that emanate from the deployment of multiple systems in the management and control of the increasing volume of data. The DMM consists of three layers, which can be employed to shape and guide actors' interaction, components' connectivity, and the use of organizational frameworks, in systems parallelism.